PARENTS’ PERCEPTIONS AND ATTITUDES TOWARDS IMPLEMENTING SCHOOL-BASED SEXUALITY EDUCATION IN SCHOOLS OF KAZAKHSTAN - Karteyeva, Ainur (Nаzаrbауеv Unіvеrsіtу Grаduаtе Sсhооl оf Еduсаtіоn, 2023)
In Kazakhstan, a traditional society with Soviet legacy, discussing sexuality topics with children and teenagers has traditionally been seen as taboo. However, social issues such as family violence, high rates of teenage pregnancies and sexually transmitted infections (STIs) demonstrate the urgent need to implement school-based sexuality education. Access to sexuality education is a fundamental right for children, and the absence of it can have critical consequences. Despite the global development and implementation of sexuality education, it is still not provided in Kazakhstan's educational system due to cultural sensitivities. ...
Keywords: sexuality education; parents’ perceptions and attitudes; Kazakhstan